Investigation the Anti-Sterility Role of Ubiquinone-10 Against Procarbazine-Induced Infertility in Male Rats - Ayyed Hameed Hassan1, Wafaa Kadhim Jasim1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Procarbazineis cytotoxic chemotherapy drug with obvious deleterious effects on male fertility. The present study aimed to investigate protective method via co-administration of Ubiquinone-10 with procarbazine to reduce harmful effects of procarbazine. Twenty- eight adult healthy male rats (3 months in age and weighing 250-300g) were randomly divided into four equal groups as following: animals of first group were received propylene glycol 20% orally and phosphate-buffered saline solution (PBS) intraperitoneally as control group while of second , third and fourth group were received procarbazine (30mg/ kg), Ubiqunone-10 (10 mg/kg) and combination of Ubiqunone-10 with procarbazine respectively, all treatments were lasted for 9 weeks. Results revealed that procarbazine induces significant increase in serum FSH and LH level while Testosterone level was significantly decreased .Similar decrease were also noticed in levels of glutathione (GSH) ,as well as activity of catalase (CAT) and superoxide dismutase (SOD) in testis . Moreover, procarbazine caused significant decrease in sperm count, motility and viability and significant increase in sperm abnormality. On the other hand, Co-administration of Ubiqunone-10 with procarbazine lead to ameliorate levels of hormone as well as to improve testicular catalase activity in addition to glutathione and superoxide dismutase levels.